Engineering interband transport by time-dependent disorder - Tayebirad, Ghazal; Mannella, Riccardo; Wimberger, Sandro (Physical review. A, Atomic, molecular, and optical physics, 2011)
We show how the evolution of atoms in a tilted lattice can be changed and controlled by phase noise on the lattice. Dependent on the characteristic parameters of the noise, the interband transport can be either suppressed or enhanced, which is of interest for very precise control in experiments with Bose-Einstein condensates. The effect of the noise on the survival probability in the ground band is summarized in a scaling plot, stressing the universality of our results.
Gesehen am 26.10.2022